Employee Motivation in Tourism Industry - Khromova, Marina (2021)
This diploma thesis deals with the issue of applicability of motivation theories in practice in the tourism and hospitality industry. The aim of this thesis is to explore the research-practice gap between HR academics and practitioners, with a focus on the motivation of employees in the tourism and hospitality sectors and the possibility of practical implications of motivation theories in motivation strategies of travel and tourism establishments. The theoretical part describes travel and tourism research, motivation and the specifics of HR management in tourism industry, motivation theories and motivation enhancing practices. The practical part is devoted to the results of conducted semi-structured interviews with HR professionals and then dives into the discussion and recommended solutions for implementing motivation theories into practice. The research has shown that HR professionals in the tourism and hospitality industry are not affected by motivation theories when designing HR practices, their primary sources of information are professional journals and colleagues from other tourism companies.